Schaum's Feedback and Control Systems Problem 13.43: S-Plane Example - Berry, Carlotta A. (McGraw-Hill's AccessEngineering., 2013)
This video shows how to find the angle and magnitude of a system given the open loop gain and a pole-zero diagram.